Implemented the Fulfillment of Voting Rights for Persons with Disabilities in the 2024 Elections. - Nursyahbani Komendangi, Rivanka Amelia; Rahim, Erman I.; Muhtar, Mohamad Hidayat (Damhil Law Journal, 2025)
This study aims to analyze the implementation of the fulfillment of voting rights for persons with disabilities by the General Elections Commission (KPU) of Gorontalo City in the 2024 Election from the perspective of constitutional law and human rights. Although Indonesia has a strong legal basis through the 1945 Constitution, the Election Law, the Law on Persons with Disabilities, and the ratification of the Convention on the Rights of Persons with Disabilities (CRPD), field practices show that significant gaps remain. Empirical data shows that voter participation by persons with disabilities only reached 59.71% of the total 834 registered voters, indicating structural and non-structural barriers that hinder the full realization of people's sovereignty. These barriers include limited physical access at polling stations (TPS), lack of supporting facilities such as braille ballot templates and sign language interpreters, information and communication barriers, low officer capacity, and social stigma. This study uses descriptive qualitative methods with interview, observation, and documentation study techniques to obtain a factual picture and identify the factors causing low participation. The research findings demonstrate the need for policy and technical reforms in election administration, increased human resource capacity, strengthened collaboration with organizations for people with disabilities, and adequate budget allocation for accessible facilities. Optimal implementation will ensure respect for the principles of inclusivity, equality before the law, and non-discrimination, while strengthening the legitimacy and quality of Indonesian democracy.